A Cross-Sectional Study Assessing the Contributions of Body Fat Mass and Fat-Free Mass to Body Mass Index Scores in Male Youth Rugby Players - Olivier Gavarry; Gregory Lentin; Patrick Pezery; Anne Delextrat; Guillaume Chaumet; Alain Boussuges; Julien Piscione (SpringerOpen, 2018)
Abstract Background In some sports such as rugby, a large body size is an advantage, and the desire to gain weight can bring young players to become overweight or obese. The aim of this study was to evaluate the prevalence of overweight and obesity and the contribution of body fat mass index (BFMI) and fat-free mass index (FFMI) to body mass index (BMI) changes among young male rugby players (15-a-side rugby). Methods The criteria of the International Obesity Task Force were used to define overweight and obesity from BMI. The method of skinfold thickness was used to assess percentage of body fat (%BF), BFMI, and FFMI. Excess body fat was defined by using BFMI and %BF above the 75th percentile. Data were grouped according to the age categories of the French Rugby Federation (U11, under 11 years; U13, under 13 years; U15, under 15 years) and to BMI status (NW normal-weight versus OW/OB overweight/obese). Results Overall, 32.8% of the young players were overweight, and 13.8% were obese. However, 53% of young players classified as obese and overweight by BMI had an excess body fat by using BFMI above the 75th percentile. FFMI increased significantly between U11 and U13 in both groups, without significant change in BMI and BFMI. Both groups had similar significant gains in BMI and FFMI between U13 and U15, while BFMI only increased significantly in OW/OB (+ 18.5%). The strong correlations between BMI and %BF were systematically lower than those between BMI and BFMI. FFMI was strongly or moderately associated with BFMI. Conclusions Chart analysis of BFMI and FFMI could be used to distinguish changes in body composition across age categories in young male rugby players classified as normal-weight, overweight, and obese by BMI.